Management of the Disrupted Airway in Children. (9th September 2020) - Hsu, Wei‐Chung; Schweiger, Claudia; Hart, Catherine K.; Smith, Matthew; Varela, Patricio; Gutierrez, Carlos; Ormaechea, Martin; Cohen, Aliza P.; Rutter, Michael J.
Abstract : Objective: Our objective was to gather data that would enable us to suggest more specific guidelines for the management of children with airway disruption. Study Design: Retrospective case series with data from five tertiary medical centers. Methods: Children younger than 18 years of age with a disrupted airway were enrolled in this series. Data pertaining to age, sex, etiology and location of the disruption, type of injury, previous surgery, presence of air extravasation, management, and outcome were obtained and summarized. Results: Twenty children with a mean age of 4.4 years (range 1 day–14.75 years) were included in the study. All were evaluated by flexible endoscopy and/or microlaryngoscopy in the operating room. Twelve (60%) children had tracheal involvement; seven had bronchial involvement; and one had involvement of the cricoid cartilage. Nine children had air extravasation, and all these children required surgical repair. Of the 11 who did not have air extravasation, only one underwent surgical repair. Complete healing of the disrupted airway was seen in all cases. Conclusion: This series suggests that if there is no continuous air extravasation demonstrated on imaging studies or clinical examination, nonoperative management may allow for spontaneous healing without sequelae. However, surgical repair may be considered in those patients with continuous air extravasation unless a cuffed tube can be placed distal to the site of injury. For children in whom airway injury occurs in a previously operated area, the risk of extravasation is reduced. This risk is also diminished if positive pressure ventilation can be avoided or minimized. Level of Evidence: 4 Laryngoscope, 131:921–924, 2021